2019
DOI: 10.1097/nmd.0000000000001091
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Medication and Recreational Drug Effectiveness in Maladaptive Daydreaming

Abstract: Maladaptive daydreaming is a proposed disorder characterized by excessive daydreaming that causes subjective distress and/or interferes with function. The daydreaming involves complex inner worlds, characters, and plots that are understood by the person as fantasy, and the daydreaming may occupy many hours per day. The disorder has good reliability and validity in studies using a structured interview and a self-report measure developed for it. To date, no information on the responses of maladaptive daydreamers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Importantly, the cross‐sectional design of this study prohibits the identification of causality in the relationship between the measured variables. However, our data add further evidence to the higher rate of concomitant psychopathology in persons with MD, as found in previous studies (Ross et al, 2019 ; Somer, Soffer‐Dudek, & Ross, 2017 ). Shared symptoms among various DSM‐5 (American Psychiatric Association, 2013 ) disorders have long troubled the mental health community (e.g., Preskorn & Baker, 2002 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Importantly, the cross‐sectional design of this study prohibits the identification of causality in the relationship between the measured variables. However, our data add further evidence to the higher rate of concomitant psychopathology in persons with MD, as found in previous studies (Ross et al, 2019 ; Somer, Soffer‐Dudek, & Ross, 2017 ). Shared symptoms among various DSM‐5 (American Psychiatric Association, 2013 ) disorders have long troubled the mental health community (e.g., Preskorn & Baker, 2002 ).…”
Section: Discussionsupporting
confidence: 91%
“…Relatedly, in a recent study on the experienced outcome of prescription and recreational psychoactive drugs among 202 MDers (Ross et al, 2019), not only were stimulants reported to have next to no positive effect on participants' daydreaming patterns, but they were also reported to increase MD symptoms. This provides initial support for the idea that the essence of the problem in MD is probably not inattention, and is in line with MDers' reports that existing treatments do not address their main symptoms and are largely ineffective in improving the MD (Bigelsen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other components are also key elements of the disorder including the ability for vivid internal visualization, the addictive and/or compulsive aspects of the disorder, and its behavioral avoidance functions. In general, the literature suggests that maladaptive daydreaming can provide avoidance from not just the effects of severe trauma, but from general stress, conflict, loneliness, and many forms of dysphoria (1–26).…”
Section: Discussionmentioning
confidence: 99%
“…Maladaptive daydreaming has been the subject of a series of previous studies (1–26). Somer and colleagues (12) found that maladaptive daydreaming is characterized by extensive daydreaming that occupies many hours per day, causes significant subjective distress and interferes with function, and is accompanied by extensive comorbidity (12).…”
Section: Clinical Feature Did MDmentioning
confidence: 99%